2003
DOI: 10.1007/s10236-003-0043-x
|View full text |Cite
|
Sign up to set email alerts
|

Migrating sand waves

Abstract: A simple mathematical model is described, which reproduces the major features of sand waves' appearance and growth and in particular predicts their migration speed. The model is based on the linear stability analysis of the flat configuration of the sea bottom subject to tidal currents. Attention is focused on the prediction of the complex growth rate Gamma that bottom perturbations undergo because of both oscillatory fluid motions and residual currents. While the real part Gammar of Gamma controls the amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…On the contrary, in the examined One possible explanation could be found in the hypothesis of a differential migration as a function of depth. More particularly, as far as field migration is concerned, Besio et al (2003a) showed that it is due to the presence of tidal constituents superposed on a main oscillatory component, which break the symmetry of the flow field close to the bottom. Quantitative results of Besio et al (2003a), who studied the effect of the superposition on M2 of either Z0 or M4, cannot be used here, because hydrodynamic characteristics are very different: although M2 is the main component, both Z0 and M4 are very small.…”
Section: Comparison Between Field Measurements and Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, in the examined One possible explanation could be found in the hypothesis of a differential migration as a function of depth. More particularly, as far as field migration is concerned, Besio et al (2003a) showed that it is due to the presence of tidal constituents superposed on a main oscillatory component, which break the symmetry of the flow field close to the bottom. Quantitative results of Besio et al (2003a), who studied the effect of the superposition on M2 of either Z0 or M4, cannot be used here, because hydrodynamic characteristics are very different: although M2 is the main component, both Z0 and M4 are very small.…”
Section: Comparison Between Field Measurements and Discussion Of Resultsmentioning
confidence: 99%
“…Then, the results of the two bathymetric surveys are described and an analysis of sand-wave geometric characteristics is reported along with a comparison between data from the two surveys. Observations are also compared with predictions of a theory (Besio et al 2003a) which relates sand-wave growth and migration to the main constituents of the forcing tides. The paper ends with conclusions and remarks about future research.…”
Section: Introductionmentioning
confidence: 99%
“…In the situation where forcing includes both the M 4 tide and a steady component, it is possible to have a migration of the bedforms against the direction of the steady current. Besio et al (2003) used this combination of currents to explain the upcurrentmigration of sand waves. A necessary condition is that the phase between the M 2 and M 4 tide is such that it introduces a residual sediment transport in the direction opposite to the residual sediment transport caused by the residual current.…”
Section: Sensitivity To Standard Deviationmentioning
confidence: 98%
“…Dredging may be required because sand waves migrate into or along shipping channels and harbors, hence reducing the local water depth and, consequently, affecting the navigability. It has been recognized that near-shore, migrating sand waves might even affect shoreline evolution and coastal defense works [1]. The presence of sand waves in some particular areas is strongly correlated to the amplitude of the spring tidal current [2].…”
Section: Introductionmentioning
confidence: 99%